مستوى الطموح وعلاقته بقلق المستقبل لدى المراهقين المتمدرسين المنخرطين بمؤسسات الشباب والرياضة - بن هدية، أحمد, اليمان، علي (جامعة الوادي university of Eloued, 2020)
ملخص الدراسة: تهدف هذه الدراسه إلى معرفه العلاقه الإرتباطيه بين مستوى الطموح و قلق المستقبل لدى المراهق المتمدرس المنخرط بمؤسسات الشباب والرياضه بالمقاطعه الاداريه تقرت . أين تضمنت هذه الدراسه فرضية عامة جاءت على النحو التالي : توجد علاقه إرتباطيه ذات دلاله إحصائيه بين مستوى الطموح وقلق المستقبل لدى المراهق المتمدرس المنخرط بمؤسسات الشباب والرياضة بالمقاطعة الادارية تقرت . وقد تفرعت من الفرضية العامة ثلاث فرضيات إجرائية مفادها: الفرضية الاجرائية الاولى: توجد علاقة إرتباطية ذات دلالة إحصائية بين مستوى الطموح وقلق المستقبل الأسري لدى المراهق المتمدرس المنخرط بمؤسسات الشباب والرياضة بالمقاطعة الادارية تقرت. الفرضية الاجرائية الثانية : توجد علاقة إرتباطية ذات دلالة إحصائية بين مستوى الطموح وقلق المستقبل المدرسي لدى المراهق المتمدرس المنخرط بمؤسسات الشباب والرياضة بالمقاطعة الادارية تقرت . الفرضية الاجرائية الثالثة : توجد علاقة إرتباطية ذات دلالة إحصائية بين مستوى الطموح وقلق المستقبل المهني لدى المراهق المتمدرس المنخرط بمؤسسات الشباب والرياضة بالمقاطعة الادارية تقرت . وقد إعتمد الباحثان في هذه الدراسة على المنهج الوصفي الإرتباطي . ليتم بعدها إختيار أفراد العينة بطريقة غرضية بالنسبة للعينة الاستطلاعية ، أما العينة الأساسية فقد تم إختيارها بطريقة عشوائيه إحتمالية و عددها 60 فردا . وبعد الإطلاع على التراث النظري لمتغيرات الدراسة قاما الباحثان ببناء مقياسان ، الأول لقياس متغير مستوى الطموح والثاني لقياس متغير قلق المستقبل . وقد قاما الباحثان بتحليل البيانات بإستخدام نظام (20) spss . وتوصلنا في الدراسة الحالية إلى ما يلي : ـ توجد علاقة إرتباطية سالبة ذات دلالة إحصائية بين مستوى الطموح وقلق المستقبل الأسري لدى المراهق المتمدرس المنخرط بمؤسسات الشباب والرياضة بالمقاطعة الادارية تقرت . ـ توجد علاقه إرتباطية سالبة ذات دلالة إحصائية بين مستوى الطموح وقلق المستقبل المدرسي لدى المراهق المتمدرس المنخرط بمؤسسات الشباب والرياضة بالمقاطعة الادارية تقرت . ـ توجد علاقة إرتباطية سالبة ذات دلالة إحصائية بين مستوى الطموح وقلق المستقبل المهني لدى المراهق المتمدرس المنخرط بمؤسسات الشباب والرياضة بالمقاطعة الادارية تقرت . ومنه فالفرضية العامة محققة والتي مفادها : ـ توجد علاقة إرتباطية بين مستوى الطموح وقلق المستقبل لدى المراهق المتمدرس المنخرط بمؤسسات الشباب والرياضة بالمقاطعة الادارية تقرت . Study summary : This study aims to know the correlation between the level of ambition and anxiety for the future of the schooled teenager involved in youth and sports institutions in the administrative district )touggourt). Where did this study include a general hypothesis that came as follows: There is a statistically significant correlation between the level of ambition and future anxiety of the schooled teenager involved in youth and sports institutions in the administrative district )touggourt). Three partial hypotheses have branched out from the general hypothesis: The first partial hypothesis: There is a statistically significant correlational relationship between the level of ambition and anxiety of the family future of the schooled teenager involved in youth and sports institutions in the administrative district )touggourt). The second partial hypothesis: There is a statistically significant correlation between the level of ambition and anxiety for the school future of the schoolgirl who is involved in youth and sports institutions in the administrative district )touggourt). The third partial hypothesis: There is a statistically significant correlation between the level of ambition and anxiety for the future career of the schooled teenager involved in youth and sports institutions in the administrative district )touggourt) The two researchers have relied in this study on the correlational descriptive approach. Then, the sample members were selected in a systematic, random way, which numbered 60 individuals. After examining the theoretical heritage of the study variables, the two researchers built two measures, the first to measure the level of ambition variable and the second to measure the variable of future anxiety The two researchers analyzed the data using the (20) spss system. The results of the study indicated the following: There is a negative correlation relationship with statistical significance between the level of ambition and anxiety of the family future of the schooled teenager involved in youth and sports institutions in the administrative district )touggourt). There is a negative correlation relationship with statistical significance between the level of ambition and anxiety for the school future of the schooled teenager involved in youth and sports institutions in the administrative district )touggourt) There is a negative correlation relationship with statistical significance between the level of ambition and anxiety for the future career of the schooled teenager involved in youth and sports institutions in the administrative district )touggourt) And through the verification of the partial hypotheses, the general hypothesis is realized: There is a statistically significant correlation between the level of ambition and future anxiety of the schooled teenager involved in youth and sports institutions in the administrative district )touggourt).
دراسة ميدانية بالمقاطعة الإدارية توقرت
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: مستوى الطموح، قلق المستقبل; Niveau d'ambition, anxiété pour l'avenir; Level of ambition, anxiety for the future